Internationales Jahrbuch für Medienphilosophie (De Gruyter (A), 2015)
The International Yearbook of Media Philosophy brings together contributions related to media philosophy, presents an invited paper by an international scholar in each volume, offers re-readings of classical philosophical texts from the perspective of media philosophy, and contains reports, dialogues, and interviews. It is aimed at philosophers, media scholars and academics.